Good Practices for Rechargeable Lithium Metal Batteries. Issue 16 (1st January 2019) - Wu, Bingbin; Yang, Yang; Liu, Dianying; Niu, Chaojiang; Gross, Mark; Seymour, Lorraine; Lee, Hongkyung; Le, Phung M. L.; Vo, Thanh D.; Deng, Zhiqun Daniel; Dufek, Eric J.; Whittingham, M. Stanley; et al.
Abstract : High-energy rechargeable lithium metal batteries have been intensively revisited in recent years. Since more researchers started to use pouch cell as the platform to study the fundamentals at relevant scales, safe testing and handling of lithium metal and high-energy lithium metal batteries have become critical. Cautions and safety procedures are needed when handling cycled pouch cells with pulverized lithium metal particles inside. From cell design, electrode preparation, cell fabrication to testing procedure, this work aims to discuss the possible root causes that may initiate cell internal short circuit and raise safety concerns. Safe transfer, disassembly and disposal of cycled Li metal pouch cells are also discussed. The insights provided in this article are applicable for the research on high-energy lithium-ion batteries as well and may inspire more safety strategies to accelerate research innovation by using large-format batteries as the testing vehicle and conduct the research safely.